Comparison Analysis of Online Shop between Lazada and Shopee on Students of The Faculty of Economics and Business (FEB) Narotama University Surabaya, Indonesia - Anarki Bayu Sadewo; R. Agus Baktiono (Yayasan Ahmar Cendekia Indonesia, 2020)
This study aims to analyze differences in consumer satisfaction in buying products through the Online Shop between SHOPEE and LAZADA among FEB students of Narotama University Surabaya seen from the perception of how to use applications, promotions, prices, and satisfaction. This type of research is comparative research with a quantitative approach. The population in this study were students of the Faculty of Economics and Business at Narotama University who had used both Lazada and Shoppe online shop applications using purposive sampling in the research sample. The research data was obtained by distributing research questionnaires on How to Use, Promotion, Price, and Customer Satisfaction, to 85 respondents. The results showed that: (1) There are differences in the variable of how to use the application between the Lazada online shop and Shopee, (2) There is no difference in the variable promotional activities carried out between the Lazada online shop and Shopee, (3) There are differences in the product price variables offered between the Lazada online shop and Shopee, (4 There is no difference in the consumer satisfaction variable in shopping through the Lazada online shop with Shopee.